OnDA: online data analysis and feedback for serial X‐ray imaging. Issue 3 (23rd May 2016) - Mariani, Valerio; Morgan, Andrew; Yoon, Chun Hong; Lane, Thomas J.; White, Thomas A.; O'Grady, Christopher; Kuhn, Manuela; Aplin, Steve; Koglin, Jason; Barty, Anton; Chapman, Henry N.
Abstract : This article describes the software package OnDA : online data analysis and feedback for serial X‐ray imaging. Abstract : This article describes a free and open‐source data analysis utility designed for fast online feedback during serial X‐ray diffraction and scattering experiments: OnDA (online data analysis). Three complete real‐time monitors for common types of serial X‐ray imaging experiments are presented. These monitors are capable of providing the essential information required for quick decision making in the face of extreme rates of data collection. In addition, a set of modules, functions and algorithms that allow developers to modify the provided monitors or develop new ones are provided. The emphasis here is on simple, modular and scalable code that is based on open‐source libraries and protocols. OnDA monitors have already proven to be invaluable tools in several experiments, especially for scoring and monitoring of diffraction data during serial crystallography experiments at both free‐electron laser and synchrotron facilities. It is felt that in the future the kind of fast feedback that OnDA monitors provide will help researchers to deal with the expected very high throughput data flow at next‐generation facilities such as the European X‐ray free‐electron laser.